(untitled) (Journal of Education and Development, 2024)
In this article, specific findings from a larger mixed-methods study that examined the leadership strategies Antiguan school principals employed to integrate technology into the curriculum are examined. In particular, the goal was to provide a greater understanding on some of the potential future applications of ICT integration in curriculum delivery, as identified by educators and school administrators. This study was anchored by the International Standards for Technology in Education (ISTE) model, an established technology leadership theoretical framework, as well as a technology integration framework, TPACK. Qualitative data were gathered from school principals and teachers through the use of semi-structured interviews (N=27). Furthermore, the qualitative data were manually coded and subjected to thematic content analysis. Regarding the future of ICT Integration in Antiguan Secondary Schools, several themes emerged such as, the need for increased online instruction, integrating AI technologies, as well as the acquisition of more advanced ICTs. The development of a contemporary technology use policy for secondary schools is one of the recommendations, along with pre- and in-service training for principals and educators.